Perancangan Sistem Informasi Guna Membantu Pengelolaan Administrasi Badan Usaha Milik Desa berbasis Web (Current Research in Education: Conference Series Journal, 2023)
Village-Owned Enterprises or often called Bumdes are business entities developed by the village government to improve the economy through the potential and needs that exist in the village. BUMDes can be managed by the village government or residents who are appointed to manage their business. Many types of businesses are managed in a village, either from selling agricultural products, equipment rental, or savings and loan cooperatives. All of them need to be managed properly, especially in administrative management. However, human resources or management in managing BUMDes have limitations in preparing financial administration reports, most of them still use conventional methods in recording reports so that it can cause comprehensive data errors. To facilitate the management of BUMDes administration, an information system is needed that can facilitate the management of BUMDes administration of a village. This study aims to analyze the design of the BUMDes administrative management information system to overcome problems related to administrative management that still uses conventional methods. This study uses Research and Development methods with qualitative techniques. Therefore, the existence of an information system for managing BUMDes administration can help and facilitate BUMDes management in managing administrative data through information system integration to minimize the risk of errors in preparing reports.